KROMOSOM STICKY PADA PADI (Oryza sativa L.) ASAL BENGKALIS TERHADAP CEKAMAN ALUMINIUM (Al) - Lestari, Endah Budi; Roslim, Dewi Indriyani; ', Herman (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Bengkalis has various soil types, one of them is acid soil. The major problem in acid soil is aluminium toxicity that can harm rice plant roots. The objective of this study was to identify sticky chromosomes in some local rice genotypes from Desa Bantan Air, Bengkalis, Riau Province grown in Al stress medium. Plant materials examined were four local rice genotypes from the Desa Bantan Air, i.e. Amat Candu, Sadani, Solok, and Yamin. All of the rice genotypes were exposed to 12 ppm Al for 72 hours in minimum nutrient culture, pH 4. Each treatment was repeated three times. Randomized Block Design was used in this research. The results showed that sticky choromosomes were only detected at Yamin genotype treated by 12 ppm Al. It concluded that the sticky chromosomes found in the local rice genotypes from Bengkalis was Yamin genotype